Bone involvement in non-congenital syphilis - Daniela Trujillo; Carlos Andrés Agudelo; Andrés Chavarriaga; Pablo Villa; Alejandro Vélez; Ricardo Cardona; Alicia Hidrón (Biomédica: revista del Instituto Nacional de Salud, 2023)
We documented two stages of bone involvement due to syphilis in two adult patients infected with human immunodeficiency virus. Bony lesions of secondary versus tertiary syphilis cannot be differentiated on clinical or radiologic grounds alone. Given the rarity of this clinical presentation, there is no consensus on treatment duration and related outcomes.